Acclimatization of Terminalia Arjuna saplings to salt stress: characterization of growth, biomass and photosynthetic parameters. (2nd January 2020) - Zafar, Zikria; Rasheed, Fahad; Delagrange, Sylvain; Abdullah, Muhammad; Ruffner, Charles
ABSTRACT: Terminalia Arjuna is an ecologically important agroforestry tree species across Central Asia where imbalance between water inputs and plant uptake is resulting in secondary salinization. Therefore, this study was conducted to evidence its survival capability under control, medium and high salt stress condition (2, 8, 16 dS m −1, respectively). Two independent experiments were conducted and various parameters such as (i) germination percentage (ii) growth and biomass production and, (iii) leaf gas exchange parameters were measured. The results showed that irrespective of salt stress treatment, germination percentage decreased significantly with increase in salt stress. However, growth parameters and biomass production in leaves, stem and roots were not impacted under medium salt stress but decreased significantly under high salt stress. Stomatal conductance decreased significantly under both salt stress treatments whereas CO2 assimilation rate and water use efficiency was not impacted by medium salt stress. Finally, an increase in biomass production was positively correlated to both increase in CO2 assimilation rate and stomatal conductance. The results showed that although germination in Terminalia arjuna was highly sensitive to salt stress, young plants can tolerate medium salt stress due to their ability to sustain CO2 assimilation rate and increased water use efficiency.